ROLE OF LEADERS IN EMPLOYEE PERFORMANCE ACHIEVEMENT (Study at the Tampan Pekanbaru District Office) - Syahsudarmi, Siti (Journal Boas : Business, Economics, Accounting And Management, 2023)
This study aims to identify whether the role of a leader enhances employee performance at the Kecamatan Tampan Pekanbaru. This research employs a qualitative method, aiming to unveil occurrences and facts that unfold during the research process and reflect the actual reality. The sampling technique employed is saturated sampling, with a total of 24 employees at the Kecamatan Tampan Pekanbaru as the sample size. From the data collected at the Kecamatan Tampan Pekanbaru, the researcher identifies the phenomenon that the role of a leader is highly essential in improving employee performance. A leader who can provide support, guidance, and effective direction to employees will positively impact their performance. Research observations indicate that the presence of a leader in the workplace enhances employee productivity, whereas the absence of a leader leads to suboptimal work and often results in delaying task completion until the last minute. The current performance assessment is still subjective and is not yet capable of accurately measuring what should be measured. As a result, the monthly performance assessment tends to be consistently positive, even though employee behavior and performance still require improvement. Interview results demonstrate that employees expect a leader to work longer hours than other employees and possess strong communication skills, ensuring that assigned tasks are explained clearly. In conclusion, the role of a leader, such as providing support, guidance, and effective communication, significantly contributes to enhancing employee performance. However, the subjective nature of performance assessment requires improvement to more accurately reflect the quality of employees' work.